RENEWAL STRATEGIES TO SUSTAIN PROFITABLE GROWTH IN PT. ADIRA DINAMIKA MULTI FINANCE, TBK (ADIRA FINANCE) - Tubagus Hanafi Soeriaatmadja; Harly Toindo (Journal of Business Strategy and Execution, 2010)
Profit and growth are the essence of a business. Without profit and growth, a company will not be able to survive in this rapid change and toughness in the industry. In order to keep it’s sustain profitable growth over its competitors in the industry, the company has build distinctive competencies in order to gain competitive advantages that favorable to its customers. These competitive advantages should also be maintained and changed if necessary according to the global trend and technology changing that impact to the business. Therefore, the company has to have renewal strategies to overcome challenges and win the market. The objective of the study is to capture how PT. Adira Dinamika Multi Finance, Tbk (Adira Finance) renews its strategies as an real example on how the theory of growth strategies written by Chakravarthy and Lorance in their book “Profit or Growth? Why you don’t have to choose” is applied. Research methodology applied is a combination of field research and desk research, where the primary data for this study gathered through interviews and justified by several supporting data which collected directly from the company.As a result of this study, the writer concludes that Adira Finance has been successfully renew its strategies from time to time and achieve tremendous sustain profitable growth for the period of 2001 – 2008. In order to sustain the company growth, Adira Finance has been performing the “protect and extend” strategy type as their main renewal strategy. Therefore, this study becomes an example of how that strategy could be applied in real business situation in Indonesia.